Optical nanoelecteromechanical systems (NEMS) devices and nano fabrication processes - Dong, Bin (2015)
This doctorate thesis focuses on the design, fabrication and testing of novel optical nanoelectromechanical systems (NEMS) devices. Specifically, a nano-actuator, a variable optical attenuator (VOA) and an optomechanical memory have been fabricated by nano-silicon-photonic fabrication processes. The first part of the thesis reports a NEMS actuator driven by optical gradient force. The optical force driven actuator realized by Q-factor modulation of the ring resonator can achieve an actuation range of 14 nm with a resolution of 0.18 nm. An optical displacement sensor is integrated to measure the actuation distance through optomechanical effects. The second part focuses on the development of a NEMS variable optical attenuator. In this design, optical attenuation is realized via a nano-waveguide-based optical directional coupler where the gap between waveguides is modulated by optical gradient force. Optical intensity can be attenuated to 10% of the original value with an actuation distance of at least 150 nm by tuning the wavelength of control light by 2 nm. The third part works on the optomechanical memory based on an optical force-induced bistability. A doubly-clamped silicon beam is actuated by the optical gradient force and bistability occurs as a result of nonlinearity of the optomechanical effects. The memory states can be switched by controlling the optical power from -10 dBm to -6 dBm. The switching speed is less than 150 ns.